Formulasi Sediaan Lip Cream Ekstrak Daun Miana (Coleus scuatellariodes [L] Benth.) sebagai Pewarna Alami - Vera Estefania Kaban; Nasri Nasri; Kasta Gurning; Hariyadi Dharmawan Syahputra; Zulmai Rani (Yayasan Literasi Sains Indonesia, 2022)
Miana leaf (Coleus scutellarioides L.) is a plant that contains anthocyanins that can provide certain dyes. The purpose of this study was to formulate miana leaf extract in lip cream preparations as a natural dye. The research method includes the manufacture of ethanol extract of miana leaves (Coleus scutellarioides L.) by maceration method. The extract formulas used were 25%, 50%, and 75%. The tests carried out included organoleptic tests, homogeneity tests, physical tests, pH tests, irritation tests and color preference tests. The results of the lip cream preparation, the results of the organoleptic examination were declared to have a semi-solid dosage form, distinctive odor and varied colors F1 pink F2 purplish red, F3 blackish red, homogeneity test results were declared homogeneous, stability test results showed that the preparation did not change shape, color and the odor of the preparation for 14 days of storage, the results of the pH test showed that the preparation was still within the permissible pH range on the use of the skin, the test results were declared non-irritating. Miana leaf ethanol extract can be made as a colorant in lip cream preparations.